Effectiveness of Aromatherapy Against Nausea and Vomiting in Patients Cancer Undergoing Chemotherapy: Literature Review - Magenda Bisma Yudha; Sri Nabawiyati Nurul Makiyah (Universitas Aisyah Pringsewu, 2021)
Cancer became the second leading cause of death in the world at about 9.6 million deaths in 2018. One of the most common treatments is chemotherapy. Chemotherapy has side effects such as nausea vomiting, stomatitis, anorexia, bone marrow damage, and alopecia. Treatment of vomiting nausea can be done through non-pharmacological therapy, namely by using aromatherapy. The review aims to find out and synthesize the scientific literature on the effectiveness of aromatherapy against nausea and vomiting in cancer patients undergoing chemotherapy. The literature search method uses the electronic databases PubMed, Proquest, Science Direct, and Google Scholar using search keywords: cancer + chemotherapy + aromatherapy + nausea + vomiting; cancer AND chemotherapy OR aromatherapy AND nausea AND vomiting. Out of a total of 3946 articles found, 30 were determined from the results of matching the title with the abstract. After removing duplicate articles, each abstract article is evaluated. The next 23 articles were obtained, read in full, and searched for relevant articles. Selected 8 articles used to be included in the final data set. A total of 8 articles use aromatherapy from various types of herbal medicinal plants such as lavender, ginger, and peppermint.. The conclusion is that aromatherapy has been shown to be effective for reducing symptoms of nausea and vomiting in cancer patients undergoing chemotherapy.Kanker menjadi penyebab kematian kedua di dunia sekitar 9,6 juta kematian pada 2018. Salah satu perawatan yang paling umum adalah kemoterapi. Kemoterapi memiliki efek samping seperti mual muntah, stomatitis, anoreksia, kerusakan sumsum tulang, dan alopecia. Pengobatan mual muntah dapat dilakukan melalui terapi non-farmakologis, yaitu dengan menggunakan aromaterapi. Tinjauan ini bertujuan untuk mencari tahu dan mensintesis literatur ilmiah tentang efektivitas aromaterapi terhadap mual dan muntah pada pasien kanker yang menjalani kemoterapi. Metode pencarian literatur menggunakan database elektronik PubMed, Proquest, Science Direct, dan Google Scholar menggunakan kata kunci pencarian: cancer + chemotherapy + aromatherapy + nausea + vomiting; cancer AND chemotherapy OR aromatherapy AND nausea AND vomiting. Dari total 3946 artikel yang ditemukan, 30 artikel ditentukan dari hasil pencocokan judul dengan abstrak. Setelah menghapus artikel duplikat, setiap artikel abstrak dievaluasi. 23 artikel berikutnya diperoleh, dibaca secara lengkap, dan mencari artikel yang relevan. Dipilih 8 artikel yang digunakan untuk dimasukkan dalam kumpulan data akhir. Sebanyak 8 artikel menggunakan aromaterapi dari berbagai jenis tanaman obat herbal seperti lavender, ginger, dan peppermint. Kesimpulannya adalah aromaterapi telah terbukti efektif untuk mengurangi gejala mual dan muntah pada pasien kanker yang menjalani kemoterapi.